IT Governance Maturity and Business Alignment: A COBIT 2019 Evaluation at RSUD ODSK - Wulyatiningsih, Toetik; Mambu, Joe Yuan (Malikussaleh University, Aceh, Indonesia, 2025)
IT is crucial for organizational performance and competitiveness, especially in healthcare, where service quality affects patient outcomes. Effective IT governance aligns investments with goals, delivers value, and reduces risks. This study assesses IT governance priorities at RSUD ODSK using the COBIT 2019 framework, identifying key governance and management objectives. The research employs a structured methodology, beginning with problem identification and then data collection through structured interviews using the COBIT 2019 Design Toolkit and the analysis of 10 Design Factors. These factors help determine the most critical governance objectives in RSUD ODSK's operational environment and strategic priorities. Findings indicate that Client Service/Stability is the hospital's top strategic priority, supported by key enterprise goals, including compliance with external regulations, business-service continuity, and internal process optimization. The prioritization process highlights Managed Assurance (MEA04) and Managed Security Services (DSS05) as the most critical governance objectives, both receiving importance scores of 100%, emphasizing the need for continuous IT performance monitoring and strong data security measures. Other highly prioritized objectives include Managed Security (APO13) at 85% and Managed Compliance with External Requirements (MEA03) at 70%, reflecting the hospital's focus on regulatory adherence and risk management. The results provide practical guidance for RSUD ODSK in improving IT governance, aligning IT with organizational goals, and ensuring reliable IT services to enhance patient care and operational efficiency. This study contributes valuable insights for hospitals seeking to strengthen IT governance using COBIT 2019.